University study abroad and graduates' employability - Giorgio Di Pietro (IZA World of Labor, 2019)
In recent decades, the number of university students worldwide who have received some part of their education abroad has been rising rapidly. Despite the popularity of international student exchange programs, however, debate continues over what students actually gain from this experience. A major advantage claimed for study abroad programs is that they can enhance employability by providing graduates with the skills and experience employers look for. These programs are also expected to increase the probability that graduates will work abroad, and so may especially benefit students willing to pursue an international career. However, most of the evidence is qualitative and based on small samples.
Keywords: I2; J6; 330; international student exchange schemes; employment prospects; international career